APPLICATION EFFICIENCY ASSESSMENT OF FORMS, METHODS, MEANS AND TYPES OF TRAINING IN CHORAL CONDUCTING LESSONS - Teriaieva, Larisa (Educological discourse, 2020)
Ukraine's entry into the European and world educational and information space requires the development and implementation of an innovative concept of education that should take into account world and domestic pedagogical and national traditions in the training of future teachers. At present stage, the formation of methodological competence of future music teachers in choral conducting has its own peculiarities, namely: ensuring interdisciplinary links of choral conducting with other professional disciplines; use of a personal approach; organization of methodological work with students; use of information technologies and computer music programs; development of personal qualities of future music teachers. Our analysis of the interdisciplinary links of choral conducting with musical disciplines showed that choral conducting has direct links with the main musical instrument, choral class, voice production, harmony, analysis of musical forms and auxiliary links with the orchestral class, additional musical instrument. The results of the scientific research confirmed that the effective methods in choral conducting are motivational, educational, practical, problem-seeking, interactive, creative and methods of control and self-control; forms of training - individual, group, practical classes, independent work, competitions of conductors, creative music competitions, pedagogical practice; effective types of training are modular, interactive, problematic, distance, programmable, and modern training means - software and methodological support of computer technologies, multimedia tools, didactic materials. Other methods, types, forms of training and aids in studying the course "Choral Conducting" are secondary and not entirely relevant.